India : International Organization of Securities Commission Objectives and Principles of Securities Regulation - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
An assessment of the level of implementation of the IOSCO principles in the Indian securities market was conducted from June 15 to July 1, 2011 as part of the Financial Sector Assessment Program (FSAP) by Ana Carvajal, Monetary and capital markets department. An initial IOSCO assessment was conducted in 2000. Since then significant changes have taken place in the Indian market, in terms of market development, upgrading of market infrastructure and of the regulatory framework. The IOSCO methodology requires that assessors not only look at the legal and regulatory framework in place, but at how it has been implemented in practice. The assessor relied on: (i) a self-assessment developed by Securities Board Exchange of India (SEBI); (ii) the review of relevant laws, and other relevant documents provided by the authorities including annual reports; (iii) meetings with the Chairman of SEBI and other members of the Board, staff of SEBI as well as the RBI, and other public authorities, in particular representatives of the Ministry of Finance (MoF) and the Ministry of Corporate Affairs (MCA); as well as (iv) meetings with market participants, including issuers, brokers, merchant bankers, fund managers, stock exchanges, external auditors, credit rating agencies and law firms.